H-1-NMR STUDY OF THE ROLE OF HEME CARBOXYLATE SIDE-CHAINS IN MODULATING HEME POCKET STRUCTURE AND THE MECHANISM OF RECONSTITUTION OF CYTOCHROME-B5 - LEE, KB; LAMAR, GN; PANDEY, RK; REZZANO, IN; MANSFIELD, KE; SMITH, KM; POCHAPSKY, TC; SLIGAR, SG (AMER CHEMICAL SOC, 1991)
H-1 nuclear magnetic resonance spectroscopy was used to assign the hyperfine-shifted resonances and determine the position of a side chain in the heme cavity of wild-type rat apocytochrome b5 reconstituted with a series of synthetic hemins possessing systematically perturbed carboxylate side chains. The hemins included protohemin derivatives with individually removed or pairwise shortened and lengthened carboxylate side chains, as well as (propionate)n(methyl)8-n(porphine-iron)(III) isomers with n = 1-3 designed to force occupation of nonnative propionate sites. The resonance assignments were effected on the basis of available empirical heme contact shift correlations and steady-state nuclear Overhauser effect measurements in the low-spin oxidized proteins. The failure to detect holoproteins with certain hemins dictates that the stable holoproteins, unlike the case of myoglobin, demand the axial iron-His bonds and cannot accommodate carboxylate side chains at interior positions in the binding pocket. Hence, the heme pocket interior in cytochrome b5 is judged much less polar and less sterically accommodating than that of myoglobin. The propionate occupational preference was greatest as the native 7-propionate site, but also possible at the nonnative crystallographic 5-methyl or 8-methyl positions. Only for a propionate at the crystallographic 8-methyl position was a significant perturbation of the native molecular/electronic structure observed, and this was attributed to an alternative propionate-protein hydrogen bond at the crystallographic 8-methyl position. The structures of the transient protein complexes detected only shortly after reconstitution reveal that the initial encounter complexes during assembly of holoprotein from apoprotein and hemin involve one of the two alternate propionate-protein links at either the 7-propionate or native 8-methyl position. In a monopropionate hemin, this leads to the characterization of a new type of heme orientational disorder involving rotation about a N-Fe-N axis.
Keywords: OVERHAUSER EFFECT MEASUREMENTS; ELECTRON-TRANSFER COMPLEX; SPERM-WHALE MYOGLOBIN; SPECTROPHOTOMETRIC ANALYSIS; FERRICYTOCHROME-B5; EQUILIBRIUM; ASSIGNMENTS; ORIENTATION; REDUCTION; PROTEINS